Socially stratified associations between self‐employment and health among Chilean older people. Issue 3 (20th January 2023) - Cabib, Ignacio; Azar, Ariel; Biehl, Andrés; Budnevich‐Portales, Carlos
Abstract: Non‐standard forms of employment, such as self‐employment, are among the most prevalent routes for older people to access the workforce. While the financial benefits of any form of self‐employment in later life have been widely acknowledged, less is known about their impact on health. This study explores the association between self‐employment and 16 health outcomes among older people with different social stratification characteristics in Chile, a developing country experiencing rapid population ageing. We rely on a rich representative life history survey of Chilean men and women between the ages 65 and 75 years ( N  = 802) living in the capital Santiago, weighted sequence analysis to reconstruct employment histories and weighted regression analysis to measure the association between self‐employment and health in later life. All our analyses are adjusted by both individual lifetime health indicators and employment trajectories. Our results show that being self‐employed relative to not working is positively associated with health in seven out of 16 outcomes. More surprisingly, those in a self‐employment position seem to enjoy better health outcomes, particularly among the less educated and lower‐income levels. These stratified associations raise questions about how these individuals enjoy better health despite facing adverse social conditions.